Antimicrobial-resistant pathogens in Canadian ICUs: results of the CANWARD 2007 to 2016 study. (29th November 2018) - Denisuik, Andrew J; Garbutt, Lauren A; Golden, Alyssa R; Adam, Heather J; Baxter, Melanie; Nichol, Kimberly A; Lagacé-Wiens, Philippe; Walkty, Andrew J; Karlowsky, James A; Hoban, Daryl J; Mulvey, Michael R; Zhanel, George G
Abstract: Objectives: To describe the microbiology and antimicrobial resistance patterns of cultured samples acquired from Canadian ICUs. Methods: From 2007 to 2016, tertiary care centres from across Canada submitted 42938 bacterial/fungal isolates as part of the CANWARD surveillance study. Of these, 8130 (18.9%) were from patients on ICUs. Susceptibility testing guidelines and MIC interpretive criteria were defined by CLSI. Results: Of the 8130 pathogens collected in this study, 58.2%, 36.3%, 3.1% and 2.4% were from respiratory, blood, wound and urine specimens, respectively. The top five organisms collected from Canadian ICUs accounted for 55.4% of all isolates and included Staphylococcus aureus (21.5%), Pseudomonas aeruginosa (10.6%), Escherichia coli (10.4%), Streptococcus pneumoniae (6.5%) and Klebsiella pneumoniae (6.4%). MRSA accounted for 20.7% of S. aureus collected, with community-associated (CA) MRSA genotypes increasing in prevalence over time ( P < 0.001). The highest susceptibility rates among MRSA were 100% for vancomycin, 100% for ceftobiprole, 100% for linezolid, 99.7% for ceftaroline, 99.7% for daptomycin and 99.7% for tigecycline. The highest susceptibility rates among E. coli were 100% for tigecycline, 99.9% for meropenem, 99.7% for colistin and 94.2% for piperacillin/tazobactam. MDR was identified in 26.3% of E. coli isolates, with 10.1% producing an ESBL. The highest susceptibility rates among P. aeruginosa were 97.5% for ceftolozane/tazobactam, 96.1% for amikacin, 94.7% for colistin and 93.3% for tobramycin. Conclusions: The most active agents against Gram-negative bacilli were the carbapenems, tigecycline and piperacillin/tazobactam. Against Gram-positive cocci, the most active agents were vancomycin, daptomycin and linezolid. The prevalence of CA-MRSA genotypes and ESBL-producing E. coli collected from ICUs increased significantly over time.